ENKRIPSI PESAN CHAT MENGGUNAKAN ALGORITMA CHACHA20 PADA APLIKASI KOMUNIKASI REAL-TIME - Dandi Darmansyah; Abdul Halim Hasugian (LPPM Universitas Abdurrab, 2025)
The advancement of communication technology has now become a crucial component in supporting the flow of information in society. With the increasing use of real-time applications, understanding the security of messages transmitted over the internet is essential to protect them from eavesdropping and data theft. The application of encryption is an initial step to enhance the security of digital communication. This study aims to implement the ChaCha20 algorithm to encrypt text messages in a communication application based on Android using the Flutter framework and Firebase backend service. Test results indicate a significant performance difference compared to the AES-CBC algorithm, where ChaCha20 offers faster encryption and decryption times as well as higher throughput. Based on these findings, the use of ChaCha20 is recommended for applications requiring high-speed and efficient data exchange. The impact of this research is expected to raise awareness and understanding of the importance of selecting the right cryptographic algorithm in building secure communication systems. Furthermore, this research is anticipated to contribute meaningfully to the development of robust communication applications against growing cybersecurity threats, especially on mobile devices.